Synergic effect of recycled aggregates, waste glass, and slag on the properties of pervious concrete - Hilal El-Hassan; Peiman Kianmehr; Davoud Tavakoli; Abdulkader El-Mir; Rahbar Sakenian Dehkordi (Developments in the Built Environment, 2023)
The properties of pervious concrete made with coarse recycled concrete aggregates (RCA), recycled fine glass (RFG), and ground granulated blast furnace slag (GGBS) were examined. Pervious concrete was produced by substituting coarse aggregates with 0–40% RCA, fine aggregates with 0–100% RFG, and cement with 50% GGBS. Results revealed that incorporating RCA and RFG decreased slump and density but increased porosity and permeability. RCA replacement had a more noticeable negative effect on compressive strength, while RFG replacement was more impactful on splitting tensile and flexural strengths. Abrasion resistance decreased upon RCA inclusion and slightly increased with RFG incorporation. The performance of pervious concrete enhanced with GGBS addition. Its clogging potential was evaluated over a 30-year simulated lifespan. Permeability could be restored to half the original level. While RCA led to lower restoration rates, RFG and GGBS inclusions improved it. Analytical models were developed to correlate and predict the properties of pervious concrete.